KERAGAAN PETERNAKAN AYAM SENTUL DI KABUPATEN CIAMIS - Sudrajat Sudrajat; Agus Yuniawan Isyanto (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2018)
The research was conducted by using literature study method. The data used in the form of secondary data obtained through literature review related to this research. The data obtained then analyzed descriptively to describe the performance of Sentul chicken farm in Ciamis Regency. Research shows that Sentul chicken is the original chicken of Ciamis Regency which has an advantage in body weight growth and egg production so it has the potential to be developed in an effort to increase the income of farmers.Keywords: Performance, Sentul Chicken, Ciamis District